AUTO- AND HETEROSTEREOTYPES AS INDICATORS OF EXPRESSIVENESS DEGREE IN PRIMARY SCHOOL AGE CHILDREN'S ETHNIC IDENTITY EMOTIONAL COMPONENT - V V Gritsenko; Yu V Brazhnik; A P Orlova (Peoples' Friendship University of Russia (RUDN University), 2016)
The article deals with the results of the empirical research devoted to the study of Russian and Belarusian primary school age children's representations about members of their (autostereotypes) and other (heterostereotypes) ethnic groups in the conditions of Russian-Belarusian border area. The study involved students of 2-3 grades from the towns Smolensk (N = 83) and Vitebsk (N = 84). The diagnostic study was carried out using a modified procedure by M. Barretta. The analysis of the results showed that auto- and heterostereotypes of the Russians and Belarusians are characterized by predominance of positive characteristics over negative ones. At the same time the decrease in the proportion of positive characteristics and the increase of the negative ones regarding the Ukrainians is marked which can be explained by the present situation in Ukraine, the influence of the media and public opinion on the primary school age children's perception of the representatives from the Ukrainian ethnic group. It is highlighted that positiveness / negativeness of the stereotypes is an indicator of the expressiveness degree of ethnic identity emotional component. The conclusion about the importance of corrective and preventive work aimed at the development of positive ethnic identity as an integral part of social identity that promotes the integrity of self-image acquisition, the formation of subjective well-being and psychological security of primary school age children is drawn.